2010
DOI: 10.2225/vol13-issue5-fulltext-22
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable lipase from a newly isolated Staphylococcus xylosus strain; process optimization and characterization using RSM and ANN

Abstract: Normal feed forward back-propagation artificial neural network (ANN) and cubic backward elimination response surface methodology (RSM) were used to build a predictive model of the combined effects and optimization of culture parameters for the lipase production of a newly isolated Staphylococcus xylosus. The results demonstrated a high predictive accuracy of artificial neural network compared to response surface methodology. The optimum operating condition obtained from the ANN model was found to be at 30ºC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Likewise, higher moisture levels than optimum value cause decreased porosity, lower oxygen transfer, and alteration in solid-state particle structure [29]. In our previous study, RSM revealed good understanding in complicated biological systems [31]. A reduced cubic-fitted model (Table 2) revealed its potential to determine the best operative conditions for G. candidum local strain lipolytic activity towards coconut oil hydrolysis and MCFA production.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, higher moisture levels than optimum value cause decreased porosity, lower oxygen transfer, and alteration in solid-state particle structure [29]. In our previous study, RSM revealed good understanding in complicated biological systems [31]. A reduced cubic-fitted model (Table 2) revealed its potential to determine the best operative conditions for G. candidum local strain lipolytic activity towards coconut oil hydrolysis and MCFA production.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the other thermostable bacterial lipases (Kim et al , 1996; Meilleur et al , 2009; Sarkar et al , 2012), ELB12 had notable specific activity. Unlike many of them (Khoramnia et al , 2010, 2011; Sarkar et al , 2012), the lipase showed less thermostability at high temperatures. Nevertheless, the specific activity of ELBn12 even after 1 h incubation at 70 °C (1000 U/mg) was remarkable and more than original activity of the many reported thermostable bacterial lipases (Khoramnia et al , 2011; Meilleur et al , 2009; Sarkar et al , 2012).…”
Section: Discussionmentioning
confidence: 84%
“…Some examples of these include thermostable lipases from Bacillus subtilis EH 37 (Ahmed et al , 2010), citrobacter freundii (Guanasekaran et al , 2006), Staphylococcus xylosus (Khoramnia et al , 2010), Acinetobacter sp. (Khoramnia et al , 2011), and Proteus vulgaris K80 (Kim et al , 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khoramnia et al (2010) published an article in the Electronic Journal of Biotechnology describing a process characterization and optimization case study. The investigators were interested in maximizing the lipase activity of a bacterial culture.…”
Section: Optimal Designs For a Nonstandard Linear Modelmentioning
confidence: 99%